Evaluation of microbial contamination of canine plasma eyedropper bottles following clinical use in canine patients. (24th May 2018) - Strauss, Rachel A.; Genschel, Ulrike; Allbaugh, Rachel A.; Sebbag, Lionel; Ben‐Shlomo, Gil
Abstract: Objective: To investigate microbial contamination of canine plasma eye drops when used clinically and to compare the effect of two different eyedropper bottles on contamination rate. Methods: Forty‐six bottles containing plasma were randomly dispensed for use on 42 dogs with ulcerative keratitis. Of these, 23 were standard eyedropper bottles and 23 were Novelia ® bottles designed to prevent contamination. After use for up to 2 weeks, samples for bacterial culture were obtained from a drop of plasma, the bottle tip, the plasma inside the bottle, and the corneal surface. Fungal culture was performed from a drop of plasma. Results: The overall microbial contamination rate was 17.4% (8/46 bottles); however, only one bottle had growth from the plasma inside the bottle. There was a lower contamination rate of Novelia ® bottles (3/23 = 13.0%) compared to standard bottles (5/23 = 21.7%), but this difference was not statistically significant ( P = .57). There were also no significant differences in contamination rate of bottles used greater than 7 days compared to less than or equal to 7 days, or in bottles used greater than 4 times daily compared to 4 times daily or less. Three corneal samples (6.5%) had bacterial growth, but none matched contamination from the bottles. Conclusions: Novelia ® bottles may decrease contamination of plasma eye drops used clinically. However, while microbial contamination of plasma bottles was documented, no clinically relevant complications were observed. This study supports safe use of plasma eye drops for up to 2 weeks when refrigerated and dispensed from either Novelia ® or standard eyedropper bottles.